2020
DOI: 10.1021/acsomega.0c02279
|View full text |Cite
|
Sign up to set email alerts
|

ElectroSens Platform with a Polyelectrolyte-Based Carbon Fiber Sensor for Point-of-Care Analysis of Zn in Blood and Urine

Abstract: In this paper, we describe an electrochemical sensing platform—ElectroSens—for the detection of Zn based on self-assembled polyelectrolyte multilayers on the carbon fiber (CF) electrode surface. The CF-extended surface facilitates the usage of a small volume electrochemical cell (1 mL) without stirring. This approach allows making a low-cost three-electrode platform. Working electrode modification with layer-by-layer assembly of polyethyleneimine (PEI), poly(sodium 4-styrenesulfonate) (PSS), and mercury nitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Previous studies have shown the possibility of immobilizing polyelectrolyte nanolayers on the surface of a carbon ber. 31 This study demonstrates a new interface: hydrophobic carbon berhydrophilic layers of polyelectrolyteshydrophobic ionselective membrane. This interface enables to propose the potential method of correlation for COVID-19 with electrochemical measurements using ion-selective electrodes to determine the sodium and potassium ion concentration change in urine and blood serum (Fig.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have shown the possibility of immobilizing polyelectrolyte nanolayers on the surface of a carbon ber. 31 This study demonstrates a new interface: hydrophobic carbon berhydrophilic layers of polyelectrolyteshydrophobic ionselective membrane. This interface enables to propose the potential method of correlation for COVID-19 with electrochemical measurements using ion-selective electrodes to determine the sodium and potassium ion concentration change in urine and blood serum (Fig.…”
Section: Introductionmentioning
confidence: 80%
“…32 Previously, we have developed a portative platform based on a carbon ber electrode for Zn detection in blood and urine samples. 31 We afforded the carbon ber electrode as a substrate for the ion-selective electrode with pseudo-liquid junction. Previous studies have shown the possibility of immobilizing polyelectrolyte nanolayers on the surface of a carbon ber.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic reduction [107] of noble metal particles on titania core [95] leads to dual-wavelength responsiveness: in the UV to near-IR regions of electromagnetic spectrum. It is possible to regulate photocatalytically (auto-catalytic) waves of enzymatic reactions [108], switch biofilm fluorescence [109], build a platform for a chemical logic device [110], and perform sustainable diagnostics [111][112][113]. The trend in the field of encapsulated systems is to combine different functions in one capsule matrix.…”
Section: Corrosion Protection Of the Coatingsmentioning
confidence: 99%
“…[10,11]. Considering that custom sensing platforms allow setting the specific parameters for a defined analyte (e.g., time, current, applied potential), a variety of electronic systems with ECS have been developed for decentralized measurements of glucose [12], H 2 O 2 [13], dopamine [14], progesterone [15], cortisol [16], zinc [17] and diagnosis of celiac disease [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the second design stage, the electronic input is linked to microcontroller (MCU) platforms like Arduino, ESP32 [14] or Raspberry Pi [19] to perform digitalization of the acquired signals, synchronize functions and configure internal operational parameters. The MCU also controls the mechanisms to store and present the acquired data by using USB communication protocols to a computer [24], wireless connection [14,18] or even cloud database [17]. Following this general approach, custom equipment has been developed in a simple and compact format to perform electrochemical techniques such as cyclic voltammetry (CV) [16,25], differential pulse voltammetry (DPV) [13,24] and amperometry (AMP) [7,12].…”
Section: Introductionmentioning
confidence: 99%